The influence of Gum Arabic on the physicochemical and antimicrobial activity of the microencapsulated Mahkota Dewa (Phaleria macrocarpa) leaves - Mohd Zin, Z.; Razman, N.H.; Hasmadi, M.; Zainol M.K.; Mohd Nazmi Abd Manap (Rynnye Lyan Resources, 2024)
Indexed by SCOPUS/MYCITE